Candida auris: A bibliometric analysis of an emerging global health threat - Paolo Ragusa; Alessandro Prinzivalli; Simone Pizzini; Giulia Libero; Giuseppina Lo Moro; Valerio Brescia; Giacomo Scaioli; Davide Minniti; Roberta Siliquini; Fabrizio Bert (Elsevier, 2023)
Background: Candida auris (CA) is an emerging fungus, classified as an urgent global health threat, that resists common antifungal drugs and decontamination procedures; identification requires specific tools; transmissibility and mortality are high in healthcare settings. Infection and colonisation can be long-lasting, leading to problems in isolation procedures and the risk of outbreaks. This study aims to evaluate publication and citation related metrics, identify major keywords and topics, and assess geographic distribution of published articles. Methods: A list of all publications containing ''Candida auris'' in all fields was extracted from Web Of Science on date 2023/01/02. Bibliometric analysis was conducted using the bibliometrix and biblioshiny packages on RStudio. Results: Total publications (TP) were 1283 with an annual growth rate of 53.91%. Total citations were 27854, with an average of 21.71 citations per paper. The core sources are 9 out of 322, according to Bradford's law. In only 42 countries where CA was identified, articles on the topic were published (89%). The origin of TP is concentrated in high-income countries (68.22%). Trending topics about CA include epidemiology, identification and resistance. Conclusion: Our analysis shows a growing interest in scientific literature on the topic of CA, led by Europe. In some countries where CA has been identified, no papers have been published. Despite the multidrug-resistance of CA, the topic of therapy is not much debated. Our findings highlight the need to increase focus on CA in order to promote health systems' preparedness and to properly address the spread of this worrisome pathogen.